2018
DOI: 10.1038/s41396-018-0319-2
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen-induced changes in floral scent may increase honeybee-mediated dispersal of Erwinia amylovora

Abstract: Honeybees are well recognised for their key role in plant reproduction as pollinators. On the other hand, their activity may vector some pathogens, such as the bacterium Erwinia amylovora, the causative agent of fire blight disease in pomaceous plants. In this research, we evaluated whether honeybees are able to discriminate between healthy and E. amylovora-infected flowers, thus altering the dispersal of the pathogen. For this reason, honeybees were previously trained to forage either on inoculated or healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 72 publications
0
31
0
Order By: Relevance
“…However, honeybees are attracted to healthy as opposed to diseased flowers. Cellini et al () suggested that this discrimination may be due to differential emissions of volatile compounds. For example, methyl salicylate, known to play a significant role in plant defence against biotrophic pathogens, is released by inoculated flowers and appears to repulse the honeybees.…”
Section: Volatiles Can Function As Direct Defences Against Plant Pathmentioning
confidence: 99%
“…However, honeybees are attracted to healthy as opposed to diseased flowers. Cellini et al () suggested that this discrimination may be due to differential emissions of volatile compounds. For example, methyl salicylate, known to play a significant role in plant defence against biotrophic pathogens, is released by inoculated flowers and appears to repulse the honeybees.…”
Section: Volatiles Can Function As Direct Defences Against Plant Pathmentioning
confidence: 99%
“…The nectar of environment exposed N. pseudonarcissus was dominated by sequences similar to Erwinia (82%) and Pseudomonas (18%). Both Erwinia and Pseudomonas have been documented in nectar environments [60,61] with both being the only two genera currently reported to be directly associated with pollinating species acting as bacterial vectors [62]. Similarly, the environment exposed D. purpurea was found to have a higher detectable OTU richness in comparison to non-environment exposed D.…”
Section: Discussionmentioning
confidence: 94%
“…The complex mixtures of volatiles produced by flowers can affect microbial community composition (Boachon et al ., ). Floral microbes can add scent compounds to flowers, and alter floral scent emission by inducing, reducing and/or even catabolizing floral chemistry (Peñuelas et al ., ; Helletsgruber et al ., ; Burdon et al., , Cellini et al ., ). Microbially‐mediated changes to key floral volatiles (e.g.…”
Section: Types Of Floral Phenotypes That Could Be Subject To These Dymentioning
confidence: 97%
“…Microbially‐mediated changes to key floral volatiles (e.g. linalool) potentially alter pollinator behavior (Burdon et al., ; Cellini et al ., ), and indeed pollinators such as bees can perceive (Rering et al ., ), respond innately, and learn to prefer or avoid microbial scents on flowers (Russell & Ashman, ). Pollinator preferences mediated by floral cues are key drivers of plant fitness and floral evolution (Schiestl & Johnson, ), thus epiphytic microbes that alter or enhance floral scent may shape plant fitness (Helletsgruber et al ., ; Burdon et al., ; Russell & Ashman, ).…”
Section: Types Of Floral Phenotypes That Could Be Subject To These Dymentioning
confidence: 99%